Application of FTIR-ATR spectroscopy on the bee pollen characterization - Anjos, Ofélia (2018)
Bee pollen contains almost all nutrients required by the human organism as well as diverse health-promoting substances. However, its composition and nutritional value greatly depend on the botanical origin. As such, it is important to develop a rapid and non-expensive methodology that allows studying its characteristics, making labelling more objective and easier. The FTIR-ATR technique was used to predict some nutritional parameters in 126 bee pollen samples. FTIR-ATR spectrum obtained in the region between 4000 and 400 cm -1 with PLS Regression models were used to correlate spectral information with the data obtained using reference methods. In this first approach with pollen samples, good correlation models with appropriate accuracy were obtained for the evaluated parameters with r 2 varying from 74.8 to 97% and residual prediction deviation between 2.0 and 5.8. These results suggest that FTIR-ATR may be a useful technique for assessing bee pollen’s composition.